I"m Somali and I"m Christian: A dilemma for religion and identity in the context of migration in Southern Africa - Mpofu, Buhle (HTS teologiese studies, 2021)
This contribution is one of a series that aimed at publishing significant findings from the research conducted for a PhD study where emerging themes were isolated and discussed. During one of the focus group conversations, Abdul (not his real name) explained how his Somali-Christian identity presented a dilemma whilst he lived with fellow Muslim Somali nationals when he was displaced during the 2015 xenophobic violence in Johannesburg. Firstly, this contribution discusses a general overview of the situation of migration and then his situation is explored from the themes, which emerged from this study from the lens of bicultural and acculturation processes of identity formation. Although this was not a representative sample of male foreign migrant experiences, analysing Abdul’s situation within a post-colonial and bicultural acculturation paradigm revealed the ‘embedded’ trajectories at the interface between religion, identity and migration in social and economic processes of transformation. Sketching Abdul’s experiences through these lenses also generated contested processes on the interface of religion and identity that reflect the significance of the role played by religion in identity constructions which are open to change (and sometimes present a dilemma), as life circumstances fluctuate with complex interactions in search of survival strategies to ward off any potential threats to a flourishing life. Such survival strategies highlight how these encounters generate hybrid identities and discourses with new boundaries, which, although fluid, volatile and situational, are reminiscent with historical and odious notions of colonialism that present African migrants as undesired foreigners whilst portraying other western and Asian migrants in cosy terms such as expatriates and tourists.Contribution: Exploring the relevance of migrant expressions within the context of identity constructions and socio-economic framework demonstrates how contested processes of socio-economic and religious transformation reflect the significance of the role played by religion on identity constructions. These constructions are articulated through fluid and complex encounters, which fluctuate to generate hybrid identities and migrant survival discourses.